Neurofeedback-Based Enhancement of Single Trial Auditory Evoked Potentials: Feasibility in Healthy Subjects. (March 2018) - Rieger, Kathryn; Rarra, Marie-Helene; Moor, Nicolas; Diaz Hernandez, Laura; Baenninger, Anja; Razavi, Nadja; Dierks, Thomas; Hubl, Daniela; Koenig, Thomas
Previous studies showed a global reduction of the event-related potential component N100 in patients with schizophrenia, a phenomenon that is even more pronounced during auditory verbal hallucinations. This reduction assumingly results from dysfunctional activation of the primary auditory cortex by inner speech, which reduces its responsiveness to external stimuli. With this study, we tested the feasibility of enhancing the responsiveness of the primary auditory cortex to external stimuli with an upregulation of the event-related potential component N100 in healthy control subjects. A total of 15 healthy subjects performed 8 double-sessions of EEG-neurofeedback training over 2 weeks. The results of the used linear mixed effect model showed a significant active learning effect within sessions ( t = 5.99, P < .001) against an unspecific habituation effect that lowered the N100 amplitude over time. Across sessions, a significant increase in the passive condition ( t = 2.42, P = .03), named as carry-over effect, was observed. Given that the carry-over effect is one of the ultimate aims of neurofeedback, it seems reasonable to apply this neurofeedback training protocol to influence the N100 amplitude in patients with schizophrenia. This intervention could provide an alternative treatment option for auditory verbal hallucinations in these patients.